2017
DOI: 10.3390/su9091670
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Emerging Trends of Financial Business Method Patents

Abstract: Financial technology has become an important part of the banking industry in recent times. This study attempts to propose a framework to identify emerging areas and trends using financial business method patents. Based on the abstracts of financial business method patents registered at the United States Patent and Trademark Office, this study first applies latent Dirichlet allocation to identify emerging topics. The probability of the annual occurrence of each topic is adjusted through the exponentially weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…This characteristic generates fluent knowledge flows, and so the statistical power and validity of patent citation frequency-based metrics are often increased. Therefore, business method patents have been widely used for many quantitative studies [15][16][17][18].…”
Section: Business Methods Patents For Accounting Information Systemsmentioning
confidence: 99%
“…This characteristic generates fluent knowledge flows, and so the statistical power and validity of patent citation frequency-based metrics are often increased. Therefore, business method patents have been widely used for many quantitative studies [15][16][17][18].…”
Section: Business Methods Patents For Accounting Information Systemsmentioning
confidence: 99%
“…However, these methods can only measure the FinTech innovation carried out by the financial sectors and cannot cover other sectors. Lee and Sohn [28] found that FinTech-related technological innovation could be found in patents, and the theme of FinTech innovation could be mined based on text analysis. However, due to the lack of annotated patents and corresponding datasets, there are few studies on FinTech patent identification based on machine learning or deep learning models.…”
Section: Related Workmentioning
confidence: 99%
“…Topic trajectory identification is a research area that has attracted significant attention from scientific institutions and innovation-industry sectors. In this area, a fundamental is the use of topic modeling to discover latent thematic topics (or concepts) from a document collection, where each topic consists of its representative terms extracted from the collection [1]. More recently, dynamic topic modeling has also been utilised to identify topics and their evolution over a time period [2,3,4].…”
Section: Motivation and Significancementioning
confidence: 99%
“…An example of M is given in Table 4. To estimate TESs in M, the concept of similarity has been widely used in most related works [9,5,11,16,1,3]. The fundamental is to formulate a similarity measure between x and y using the aggregated similarities between x's top-k descriptive terms and y's top-k descriptive terms (often K=10) [19,3].…”
Section: Input Data Formatmentioning
confidence: 99%